The Relationship Between the Implementation of Clean and Healthy Living Behaviors and the Incidence of Stunting in Toddlers - Uswatun Hasanah; Siti Arifah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Clean and healthy living behaviour is one way to reduce toddler stunting rates. Good Clean and Healthy Living Behavior at the household level can protect toddlers from infectious diseases that can interfere with the absorption of nutrients in children. The incidence of stunting in toddlers in Boyolali Regency in 2022 was 20.0%. This study aimed to determine the relationship between the incidence of stunting in toddlers and Healthy Living Behavior. This study is a quantitative study with a cross-sectional design. This research was conducted at the Boyolali Health Center, precisely at the Sawit 1 Health Center, Boyolali Regency, which was carried out in June 2024. This study's population were mothers with toddlers aged 1 to 5 years at the Sawit 1 Health Center, Boyolali Regency. The population in this study was 203 people. The sampling technique for the study was Proposive random sampling, so the sample in this study was 105 mothers who had toddlers aged 1-5 years in the work area of the Sawit Health Center, Boyolali Regency. The instruments used in this study were height measurements in the form of anthropometry and a clean and healthy lifestyle questionnaire conducted in the form of direct interviews. Analysis of research data using Bivariate analysis of the chi-square test with data processing using SPSS software version 27. The study's results showed no relationship between mothers' clean and healthy lifestyle behaviour and the incidence of stunting in toddlers, with a value of p = 0.266 (p => 0.05). Mothers of toddlers are advised to maintain cleanliness and pay attention to the nutritional intake of toddlers. Health workers need to continue providing education on parenting patterns, nutrition, and access to health services. A holistic approach is still needed for comprehensive stunting prevention. Keywords: Clean and Healthy Lifestyle Behavior, Toddlers, Stunting